Feasibility Analysis of Pulse Sales and PPOB Payment Business: Yuli Pulsa Case Study - M. Fadlan Irfan Damanik; Azwan Bastian; Aji Haviz; Nasution, Hasbiyana; Chrisna, Heriyati (Journal of Economics, Assets, and Evaluation, 2024)
This study aims to analyze the feasibility of a business in selling credit and PPOB (Payment Point Online Bank) payment services at UMKM Yuli Pulsa in Binjai City. The study covers business feasibility in marketing, technology and financial aspects to see the potential for profitability and business sustainability. The analysis method used involves a data-based and systematic approach to evaluate relevant business strategies. The results of the study indicate that marketing strategies such as providing discount coupons and using banners are effective in increasing customer attraction. The use of technology through the Fazz Agent application and social media supports operational efficiency and expanding market reach. In terms of finance, the payback period is estimated at 3 years 3 months 3 weeks, reflecting positive profit prospects